Theoretical method for determination of the impact of parasitic torques from the equivalent scheme of induction machines fed by PWM inverter. (February 2021) - Markovic, Nenad; Bjelic, Slobodan; Markovic, Filip; Markovic, Marko; Jovic, Srdjan
Highlights: Determining the influence of parasitic induction torques. Analyzing the quantities and parameters of equivalent schemes of induction machines. Comparing the real values of resistance parameters of induction machines. Method presented in the paper is verified by an adapted simulation performed. Abstract: This paper presents a theoretical method for determining the impact of parasitic induction torques analyzing the quantities and parameters of equivalent schemes of induction machines fed by PWM inverter. Tested are three-pased and one-phase induction machines of different parameter and power types. For the fundamental values of power supply from PWM invertor and for important parameters of tested induction machines, comparation of results has been made, of simulation of electrical (stator and rotor current) and mechanical sizes (number of rotation and parasitic torque) of equivalent schemes of induction machines with squirrel cage and wound (phase) rotor are adopted. Theoretic model contains a correction factor, defined as relation of supply power and electro-engine force of induction machine when the rotor is stable. Comparing the real values of resistance parameters of induction machines and values obtained, taking into account a correction factor, certain discrepancies could be observed between values calculated by equivalent T and Г scheme for both groups of machines which do not exceed a value of 5%. Obtained formulas calculated according to equivalent Г schemes could be used for determination of short circuited currents. They are also used for analysis of properties of electric motors, usually for determination of currents that electric motors in the case of short circuits inject into electric network, as well as for the calculation of operating, mechanical and electrical characteristics of induction machines. Adapted simulation in the software package Matlab-Simulink in the sub-program psbupwm.mdl, replaced missing laboratory equipment, which has been used to perofm comparing of results of matematical method of such a system.